In-hospital progression to incarceration of a known peritoneal dialysis catheter-site incisional hernia: a diagnostic dilemma in a patient with recurrent uremic gastropathy - Salina Subedi; Sushan Ghimire; Sushil Mishra; Mrigendra Raj Pandey (International Journal of Surgery Case Reports, 2026)
Introduction and importance: An incisional hernia at a continuous ambulatory peritoneal dialysis (CAPD) catheter site is a well-recognized complication, with a reported incidence of 12%–40%. Incarceration of such a hernia can be life-threatening. Case presentation: A 32-year-old woman with end-stage kidney disease (ESKD) on CAPD for a year, with a reducible CAPD-site hernia, presented with recurrent epigastric pain, nausea, and vomiting. Initial differential diagnoses included uremic gastropathy, acute pancreatitis, and peptic ulcer disease. Because the symptoms were nonspecific, the hernia was reducible, and the patient refused any investigations and interventions, conservative management was initially pursued. Serial clinical reassessment demonstrated progression of the hernia to an irreducible state. Abdominal radiography showed multiple air-fluid levels, and contrast-enhanced computed tomography revealed a small-bowel obstruction due to an incarcerated CAPD-site incisional hernia. The patient underwent emergency laparotomy with release of the obstruction, on-lay mesh repair, and CAPD catheter removal, with subsequent transition to hemodialysis. Follow-up was uneventful, with satisfactory wound healing, no hernia recurrences, and a functional arteriovenous fistula. Discussion: In patients with ESKD, gastrointestinal symptoms may overlap with evolving surgical pathology. This case illustrates the in-hospital progression of a previously reducible CAPD-site hernia to acute incarceration, complicated by uremic gastrointestinal symptoms and the patient’s refusal of investigations. Conclusion: Clinicians should maintain a low threshold for clinical evaluation, imaging, and surgical evaluation in patients with ESKD and a previously known hernia.